223k views
5 votes
6. Which expression is equivalent to 2(35 – 4) – (89 + 3)?

A. -2g - 1
B. -2g - 5
C. -2g - 7
D. -2g - 11

User Shakena
by
5.1k points

1 Answer

2 votes

Answer:

Explanation:

Following order of operations rules srequires that we do any work inside parentheses first. Thus, (35 - 4) = (31), and (89 + 3) = (92). Then:

2(35 – 4) – (89 + 3) = 2(31) - (92) = -60

Have you by any chance mixed "g" with "9?" Double check this and submit this question again, please.

User Okay Zed
by
4.5k points